Emerging Role of Viral Infection in Periodontal Disease - Alaa W. Izzat; Batool Hassan Al-Ghurabi; Lina Sami Adham; Zahraa F. Shaker (Dentistry 3000)
Periodontal disease is primarily linked to a bacterial infection, such as dental plaque, which harbors a broad microbial community and can induce numerous inflammatory responses in periodontal tissue.  In numerous instances, the local bacterial incursion and host-mediated immune reactions result in severe alveolar bone resorption. While researchers mainly concentrate on identifying periodontopathogenic bacteria, recent investigations have suggested that several viruses may also play a role in the onset and advancement of periodontitis.  Human viruses can induce cytokine release from both inflammatory and non-inflammatory cells, hence compromising periodontal immune protection. This review investigates the potential role of viral infection in the pathogenesis of periodontal disease.